A Constellation of Rare Findings in a Case of Goldenhar Syndrome - Mitesh Bedi; Rakesh Kumar Jain; Vipin Kumar Barala; Abhimanyu Singh; Hiranmayi Jha (Case Reports in Pediatrics)
An 18-month-old child presented with right macrostomia, bilateral preauricular skin tags, bilateral CTEV, squint in bilateral eyes, thoracic vertebral anomalies, right sided aortic arch, and associated left pulmonary agenesis. The patient did not have any associated respiratory symptoms. Ipsilateral pulmonary agenesis is considered as a rare association with Goldenhar syndrome and a case of contralateral pulmonary aplasia has been described as an even rarer association.